(3eSGHbI JgGeI GdKbGajI GdcHQi GdChdi (B1398 (3g`(B-1978 (3es (3eNJGQGJ ef ELGHGJ GdeJSGHbjf (B/s - (3GdYKeGf, YHO GdQMef Hf YHO GdYRjR,s 1359 (3g`(B-s ((3LOI, GdSYhOjI (B:s (3JgGeI ddfTQ,s, 1978)
(3jJfGhd GdcJGH GdeSGHbI GdKbGajI, YHGQI Yf GKfjf hKdGKjf SDGd JJfGhd LhGfH KbGajI aj GdacQ hGdJQGK hGdGbJUGO hGdUfGYI hGdYdhe(B.s
Keywords: (3GdeYGQa GdYGeIs -- (3GNJHGQGJ, CSFdI, EdN(B.s